Physical Activity and Chronic Diseases in Children - Oudak, Mohamed; Rebouh, Salah; Darredoune, Kenza (sports creativity, 2025)
Physical activity is a stimulating factor in a child's growth, beneficial not only physically, but also intellectually and socially. It is our duty to offer everyone the opportunity to participate in sports, including—and perhaps especially—children with disabilities or chronic illnesses. The aim of this article is to demonstrate the benefits of physical activity in certain chronic conditions and to propose some strategies to ensure that these children are less frequently "exempted from sports." We will review the current state of knowledge on the benefits of regular sports participation in some chronic conditions that general practitioners may encounter. Introduction: Sport is necessary for children, but not just any sport, and not in any way.1 It is our duty to offer everyone the opportunity to participate in sports, including—and perhaps especially—children with disabilities or chronic illnesses.2 This is far from being the case. The benefits extend beyond health to social integration: these children often suffer from low self-esteem and difficulties integrating into school. Offering them a sporting activity provides a rewarding experience that helps them feel more normal. Depriving them of this contributes to their marginalization.3 The aim of this article is to demonstrate the benefits of physical activity in certain chronic conditions and to propose strategies to reduce the frequency with which these children are excluded from sports. We will consider the following chronic conditions as examples: epilepsy, obesity, diabetes, asthma, and juvenile idiopathic arthritis. Finally, we will discuss adapted physical activities (APA) for hospitalized children with particularly severe conditions, to show that even in these situations, beneficial strategies can be implemented.